Pengembangan E-Modul Mata Pelajaran Instalasi Penerangan Listrik untuk Pembelajaran Daring - Luthfil Hirzan; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Electrical Lighting Installation is a training course that is studied by class XI students in the Electrical Power Installation Engineering skill competency of SMK. In the learning process students find it difficult to learn the material provided by the teacher. In connection with the current situation, namely the Corona or Covid-19 Pandemic. The government makes social distancing policies. To that end, several schools stopped the face-to-face learning process. As a substitute for students having to take part in distance learning or online, it is important to have online or distance learning media that students use independently and maintain their enthusiasm for learning. This study aims to produce a product in the form of an e-module using the Sigil software in a valid and practical IPL training course. The research subjects were IPL E-Module class XI TITL in SMK. The research method used is Research and Development with reference to the Borg and Gall model. Based on the research results, the validity of the e-module of the Electrical Lighting Installation from three validators consisting of 1 media expert lecturer, 1 material expert and 1 IPL training subject teacher obtained an average achievement level of 93% with the very valid category. Practicality Test with respondents consisting of two IPL training subject teachers obtained an average achievement level of 90% with the category very practical. From the research data described, it can be concluded that the e-module learning in the IPL training course is valid and practical.